Religious Leaders And Peace Building: The Role of Tuan Guru and Pedanda in Conflict Resolution in Lombok – Indonesia - S Suprapto (Al-Jami'ah: Journal of Islamic Studies, 2015)
In some situations where the state is too weak to gain trust from the people, religious leaders have a significant role in maintaining social harmony. In many cases of the social unrest as what happened in Lombok, Tuan Guru and Pedanda played important roles in building a peaceful condition. Tuan Guru and Pedanda with their authorities have vital influences in calming down their Muslim and Hindu communities respectively. With their own ways, they were able to localize conflict issues, so much so that the social conflicts did not escalate to become greater massive riot. This article describes a number of efforts made by Tuan Guru and Pedanda  to establish peace in Lombok, such as: calming down the followers; localizing issue to reduce mass panic; reminding members of the family or community to resist social prejudice; socializing religious teachings especially the need to forge harmony; promoting “Semeton Sasak and Batur Bali” as a value of brotherhood among Balinese-Hindu and Sasaknese-Muslim; creating social sanctions against those who violated the agreements among communities; and improving the effectiveness of customary law known as awik-awik.[Pemimpin atau tokoh agama memiliki peran signifikan dalam merawat harmoni social, terutama di saat negara kurang memperoleh kepercayaan dari rakyat. Dalam sejumlah kasus kerusuhan social yang terjadi Lombok, Tuan Guru dan Pedanda memainkan peran penting dalam menciptakan kedamaian. Dengan otoritas mereka, Tuan Guru dan Pedanda mampu menenangkan massa. Dengan caranya sendiri, mereka mampu melokalisasi isu, sehingga eskalasi konflik tidak meluas menjadi kerusuhan yang massif. Artikel ini mendeskripsikan sejumlah upaya yang dikembangkan oleh Tuan Guru dan Pedanda dalam rangka bina damai di Lombok, seperti menenangkan jamaah; melokalisasi isu konflik agar massa tidak panic; mengingatkan keluraga atau anggota komunitas untuk menahan diri; mensosialisasikan nilai-nilai harmoni dalam agama, mempromosikan konsep “Semeton Sasak and Batur Bali” sebagai sebuah nilai persaudaraan antara orang Hindu-Bali dan Sasak-Muslim; menciptakan sanksi sosial bagi mereka yang melanggar kesepakatan bersama; dan meningkatkan efektifitas hukum adat yang dikenal dengan sebutan awik-awik.]